The impact of barbiturate therapy in children with severe traumatic brain injury (TBI) - Appiah-Baiden, Andrew (Division of General Surgery, 2025)
INTRODUCTION: There are no clear guidelines on how to use sedation and second-tier therapies for the treatment of raised intracranial pressure (ICP) in children with severe traumatic brain injury (TBI). Specifically, evidence is limited on the use of barbiturate therapy as a second-tier treatment option for uncontrolled ICP in children, in part because cohort sizes are small and there are little data on physiological effects. To address this, we evaluated the impact of thiopentone on physiological variables and outcome in children with severe TBI. METHODOLOGY: In this retrospective study we collected data on children (<13 years) with severe TBI who had undergone multimodality monitoring and received thiopentone to control ICP. We examined 1) the effect of thiopentone on physiological variables, 2) clinical characteristics of the cohort, and 3) outcome. RESULTS: Data were analyzed from 74 children: most were male (67.6%), and most were road traffic accident victims (71.6%). The average time from admission to initiation of thiopentone therapy was 48 hours; the average treatment duration was 4.8 days. On average, patients were extubated 5.3 days after cessation of thiopentone infusion; 20.3% received tracheostomies, and the average duration of ICU stay was 13 days. Decompressive craniectomy (DC) was used in 23% of patients. The mortality rate was 20.3%. Thiopentone use was associated with a reduction in median ICP and median mean arterial pressure (MAP), and no change in cerebral perfusion pressure (CPP). Brain tissue oxygenation was slightly higher on thiopentone, but not significantly. CONCLUSION: This is the largest study to analyze barbiturate therapy in children with TBI. Thiopentone was useful in decreasing ICP. Although there was an associated decrease in MAP, CPP remained similar. Despite this being a selected group of patients on second-tier therapies, the mortality rate was acceptable. Thiopentone use may avoid the surgical morbidity of DC, but at the expense of longer stays in ICU.